2008
DOI: 10.3155/1047-3289.58.4.530
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Regenerable System Employing Silica-Titania Composites for the Recovery of Mercury from End-Box Exhaust at a Chlor-Alkali Facility

Abstract: The release of mercury to the environment is of particular concern because of its volatility, persistence, and tendency to bioaccumulate. The recovery of mercury from end-box exhaust at chlor-alkali facilities is important to prevent release into the environment and reduce emissions as required by NESHAP (National Emission Standards for Hazardous Air Pollutants). A pilot-scale photocatalytic reactor packed with silica-titania composite (STC) pellets was tested at a chloralkali facility over a 3-month period. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The combined material is herein referred to as a silica-titania composite (STC). This material has been studied for use in a variety of photocatalytic applications such as mercury removal from flue gas [7,8], mercury recovery from caustic exhaust emitted from the chlor-alkali industry [9], and the degradation of volatile organic compounds in gas emitted from pulp and paper mills [10]. While optimal material conformations were found for the applications listed, it was not well-understood how the material characteristics changed with HF concentration and TiO 2 loading.…”
Section: Introductionmentioning
confidence: 99%
“…The combined material is herein referred to as a silica-titania composite (STC). This material has been studied for use in a variety of photocatalytic applications such as mercury removal from flue gas [7,8], mercury recovery from caustic exhaust emitted from the chlor-alkali industry [9], and the degradation of volatile organic compounds in gas emitted from pulp and paper mills [10]. While optimal material conformations were found for the applications listed, it was not well-understood how the material characteristics changed with HF concentration and TiO 2 loading.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the breakthrough curve for GH HT continues to improve over time. A potential layering effect (nucleation), whereby oxidized and adsorbed mercury is participating in the removal of the influent Hg 0 has been seen in other works employing silica-titania composites can begin to explain these results [59].…”
Section: Graphite As a Comparison For Aromatic Structurementioning
confidence: 73%
“…Numerous studies have previously reported that the presence of UV (regardless of the intensity) at the initial stage is essential to trigger the photocatalytic reaction by TiO 2 [11][12][13][14][15][16]23,24]. As shown in Fig.…”
Section: Irradiation Sourcementioning
confidence: 95%